Absolute essentials of entrepreneurship - Fuller-Love, Nerys (Milton Park, Abingdon, Oxon : Routledge, 2020)
Entrepreneurship is a fundamental business discipline and a phenomenon that drives economic growth globally. This shortform textbook focuses on the absolute essential elements of the field, covering theory and practice. Illuminating the development of entrepreneurship, the author also concise introduces the entrepreneurial personality and some of the additional hurdles faced by female and minority entrepreneurs. The central role of creativity, innovation and culture are also examined as well as entrepreneurial strategies for finance and marketing. This short text provides a unique expert overview for students of entrepreneurship, whilst the practical insights will also be useful in applications for budding entrepreneurs.
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Small Business